The Effects of Uncertainty Disclosures on REIT Returns - Sahin, Olgun Fuat; Koch, Ethan (Journal of Applied Business and Economics, 2023)
We examine the relationship between uncertainty-related disclosures in annual filings and market returns of REITs. We search annual filings (10-K) of Real Estate Investment Trusts (REITs) with the Securities and Exchange Commission (SEC) for uncertainty words. We then form rolling portfolios of REITs based on occurrences of uncertainty words in annual filing and track the returns. Our main finding is that there are no statically significant abnormal returns to these REIT portfolios. This supports the notion that the stock market is efficient in quickly incorporating any new information revealed in annual reports when the information becomes available.